The story of Wānanalua: Stranded whales and contested marine sovereignties in Hawai'i. (June 2021) - Ritts, Max; Wiebe, Sarah M
This paper considers how systems of interspecies knowing and care in Hawai'i push against state-supported frameworks of liberal biopolitical governance. In 2015, the National Oceanic and Atmospheric Administration (NOAA) issued a citation two Kanaka Maoli (Native Hawaiian) women under the Marine Mammal Protection Act, for unlawfully "tak[ing] and/or or transporting" a stranded melon-headed whale ("Wānanalua"). In the lawsuit, prosecutors deliberated on the legality of the traditional sea burial situating it within a broader context of cultural accommodations granted by National Oceanic and Atmospheric Administration. From our examination of the lawsuit, we develop the argument that marine mammal care operates in Hawaiʻi as a regulatory device for ordering interspecies relations and for pacifying Indigenous demands for greater marine political authority. To combine these claims, we consider the relation between two governance logics: liberal "recognition, " wherein accommodations regarding culture are extended to previously disenfranchised social groups, and biopolitics, pertaining in the present case to care practices governing more-than-human actors and environments. Our arguments are supported by detailed case files and interviews with local informants, including the Kanaka women accused of mishandling Wānanalua. The "ruptures" marking the Wānanalua case suggest a liberal recognition framework whose failures are connected to the biopolitics it embraces, but with an added detail: The present story reflects on how an interspecies biopolitics—an attempted management of Kānaka-whale care practices—structures strategies of liberal recognition.